2011
DOI: 10.1097/aud.0b013e31821348ae
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Analysis of Language and Speech Skills in 4- to 5-Yr-Old Children With Hearing Loss

Abstract: Results indicated that overall, children with all degrees of hearing loss who were fit with hearing technology and who received auditory-based rehabilitation services during the preschool years demonstrated the potential to develop spoken language communication skills. As a group, children with CIs and children with HAs did not differ significantly on language abilities although there were differences in articulation skills. Their performance at age 4 to 5 yrs was delayed compared with a group of hearing peers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
2
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 37 publications
4
60
2
4
Order By: Relevance
“…The accuracy and range of different types of consonant clusters (blends) produced by the children was not reported. Fitzpatrick, Crawford, Ni, and Durieux-Smith (2011) reported that around half of 32 children with severe/profound HL (including children with early and later identifi ed HL) achieved standard scores within the normal range using the GoldmanFristoe Test of Articulation-2 (GFTA-2) (Goldman & Fristoe, 2000). Collectively, such reports suggest that children with early-identifi ed HL can develop clear, intelligible speech like their typicallydeveloping hearing peers.…”
Section: Introductionmentioning
confidence: 87%
“…The accuracy and range of different types of consonant clusters (blends) produced by the children was not reported. Fitzpatrick, Crawford, Ni, and Durieux-Smith (2011) reported that around half of 32 children with severe/profound HL (including children with early and later identifi ed HL) achieved standard scores within the normal range using the GoldmanFristoe Test of Articulation-2 (GFTA-2) (Goldman & Fristoe, 2000). Collectively, such reports suggest that children with early-identifi ed HL can develop clear, intelligible speech like their typicallydeveloping hearing peers.…”
Section: Introductionmentioning
confidence: 87%
“…7,[12][13][14] Epidemiologic data confirm that >90% of children with hearing impairment are born to parents with normal hearing. 15 Although there is substantial evidence that children with hearing loss can develop oral language skills, 7,14,16 there is no consensus about optimal interventions. 17 There is a common expectation that children receiving oral language intervention should develop better language skills than those who are also exposed to sign language, which might disrupt or delay spoken language acquisition.…”
Section: Resultsmentioning
confidence: 99%
“…10,11 Although there is wide recognition that various options should be available to families, 2 events in the past two decades (newborn hearing screening and cochlear implant technology) have made it possible for even children with profound deafness to develop spoken language. 7,[12][13][14] Epidemiologic data confirm that >90% of children with hearing impairment are born to parents with normal hearing. 15 Although there is substantial evidence that children with hearing loss can develop oral language skills, 7,14,16 there is no consensus about optimal interventions.…”
mentioning
confidence: 99%
“…However, as demonstrated in a recent review (Stevenson, Kreppner, Pimperton, Worsfold, & Kennedy, 2015), very few studies include preschool children. Though language problems tend to be more severe in children with profound hearing loss than in HH children (Fitzpatrick, Crawford, Ni, & Durieux-Smith, 2011), the association between degree of hearing loss and psychosocial problems is less clear. Whereas one study reports little relationship between degree of hearing loss and prevalence of diagnosable mental health problems ), another study suggests that higher degree of hearing loss predicted psychosocial adjustment problems in elementary, secondary, and high school students (Polat, 2003).…”
Section: Psychosocial Problems In Hh Childrenmentioning
confidence: 95%
“…Degree of hearing loss has frequently been reported as a predictor to language development, but not to psychosocial outcomes Fitzpatrick, Crawford, Ni, & Durieux-Smith, 2011); suggesting that language development and psychosocial development follow different developmental paths, despite the often reported correlation between the two.…”
Section: Languagementioning
confidence: 99%